2007
DOI: 10.1128/iai.01945-06
|View full text |Cite
|
Sign up to set email alerts
|

TheNeisseria meningitidisCapsule Is Important for Intracellular Survival in Human Cells

Abstract: While much data exist in the literature about how Neisseria meningitidis adheres to and invades human cells, its behavior inside the host cell is largely unknown. One of the essential meningococcal attributes for pathogenesis is the polysaccharide capsule, which has been shown to be important for bacterial survival in extracellular fluids. To investigate the role of the meningococcal capsule in intracellular survival, we used B1940, a serogroup B strain, and its isogenic derivatives, which lack either the caps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
140
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(150 citation statements)
references
References 46 publications
10
140
0
Order By: Relevance
“…We showed that mutants of Klebsiella pneumoniae lacking CPS were more sensitive to APs than wild-type strains (Campos et al, 2004). A higher susceptibility of a Neisseria meningitidis CPS mutant to APs was also observed (Spinosa et al, 2007). Mechanistically, it has been speculated that CPS would act as a protective shield on the bacterial surface (Campos et al, 2004;Spinosa et al, 2007).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…We showed that mutants of Klebsiella pneumoniae lacking CPS were more sensitive to APs than wild-type strains (Campos et al, 2004). A higher susceptibility of a Neisseria meningitidis CPS mutant to APs was also observed (Spinosa et al, 2007). Mechanistically, it has been speculated that CPS would act as a protective shield on the bacterial surface (Campos et al, 2004;Spinosa et al, 2007).…”
Section: Introductionmentioning
confidence: 89%
“…We and others have suggested that surface-bound CPS may act as a protective shield on the bacterial surface against APs (Campos et al, 2004;Spinosa et al, 2007). In this Table 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, two capsule genes, NMB0068 (siaC) and NMB0067 (siaD), were found to have been upregulated 2.57-fold and 2.20-fold, respectively, after 30 min of LL-37 treatment, while lipA (encoding a capsule polysaccharide modification protein) was upregulated 1.3-fold after 30 min but not after 60 min. Spinosa et al (26) also found that lipA was upregulated 1.6-fold in response to treatment with sublethal concentrations of LL-37. We verified the altered gene transcription data by performing real-time RT-PCR using bacteria treated with sublethal concentrations of LL-37.…”
Section: Vol 191 2009mentioning
confidence: 95%
“…The neisserial capsule protects bacteria from LL-37. It has previously been shown that capsule polysaccharides from gram-negative bacteria contribute to resistance to AMP (3,26). In particular, Spinosa et al (26) demonstrated that the capsule plays a key defensive role, protecting intracellular serogroup B N. meningitidis from various AMPs.…”
Section: Vol 191 2009mentioning
confidence: 99%